2018
DOI: 10.1007/s00268-018-4771-y
|View full text |Cite
|
Sign up to set email alerts
|

General Thoracic Surgery in Rwanda: An Assessment of Surgical Volume and of Workforce and Material Resource Deficits

Abstract: Lack of specialist providers and material resources limits thoracic surgical volume in Rwanda despite current interventions. A targeted approach addressing barriers described is necessary for sustainable progress in thoracic surgical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Nevertheless, the dismal outcomes without surgery in patients without newer chemotherapeutic options underscores the need to support and develop thoracic services in resource-poor settings and TB endemic countries, where they are hardly ever available. 33 , 34 , 35 , 36 It is also important to appreciate that there are no randomised controlled trials comparing surgery with medical therapy versus medical therapy alone, and meta-analyses of observational studies have considerably underrepresented TB endemic countries. 14 , 37 , 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the dismal outcomes without surgery in patients without newer chemotherapeutic options underscores the need to support and develop thoracic services in resource-poor settings and TB endemic countries, where they are hardly ever available. 33 , 34 , 35 , 36 It is also important to appreciate that there are no randomised controlled trials comparing surgery with medical therapy versus medical therapy alone, and meta-analyses of observational studies have considerably underrepresented TB endemic countries. 14 , 37 , 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…In Malawi, ventilators and end-tidal carbon dioxide monitoring were routinely absent in operating rooms [44]. In Rwanda, thoracic surgical training and mentorship have increased capacity for thoracic procedures; however, equipment such as bronchial blockers and double-lumen endotracheal tubes were not readily available for single-lung ventilation [45].…”
Section: Anesthesia Techniquesmentioning
confidence: 99%
“…Further, surgical residencies increased their mean annual intake from four to 13 postgraduate students, and trained surgeons have since been distributed to hospitals in urban and rural locations [65]. To meet the need for subspecialized care, the program expanded surgical residency programs to include subspecialty training, recruited subspecialty experts for focused training and mentorship, and developed a surgical simulation center [45,74]. Ultimately, HRH made significant progress towards a strong, sustainable workforce that is increasingly prepared to treat the surgical needs of the Rwandan population.…”
Section: Human Resources For Healthmentioning
confidence: 99%
“… 9 However, studies have suggested that LMICs lack the proper training, equipment, and resources to adequately manage thoracic surgical cases. 10 Thoracic surgical cases account for nearly 10% of the unmet surgical need in some African countries. 10 Although noncommunicable diseases are expected to exacerbate this burden in the coming years, infectious and inflammatory etiologies constitute the majority of the current thoracic surgical need in LMICs.…”
mentioning
confidence: 99%